2006
DOI: 10.1002/chin.200626164
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation of Chiral Diamines via Red‐Al Reduction of N‐Boc‐Protected Amino Acid‐Derived Secondary Amides.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The unwanted side reaction, the reduction of the carbamate, has been reported with reductions using LiAlH 4 as reductant13, 14, in the literature, no such problems have been mentioned when using Red‐Al however10. It seems that the presence of aNCH 2 CH 2 OH moiety is beneficial for the selectivity of the reduction, in view of the fact that in the synthesis of 3 , 5 and 13, this side reaction was not observed.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The unwanted side reaction, the reduction of the carbamate, has been reported with reductions using LiAlH 4 as reductant13, 14, in the literature, no such problems have been mentioned when using Red‐Al however10. It seems that the presence of aNCH 2 CH 2 OH moiety is beneficial for the selectivity of the reduction, in view of the fact that in the synthesis of 3 , 5 and 13, this side reaction was not observed.…”
Section: Resultsmentioning
confidence: 94%
“…The products 7 and 8 formed were reduced using sodium bis(2‐methoxyethoxy)aluminum hydride solution (Red‐Al), in lieu of borane. The rationale behind this method was based on a report by Voight et al 10, who reported the use of Red‐Al for the synthesis of N ‐Boc‐protected amino acid‐derived secondary amines. The chiral integrity of the Phaol moiety was not affected by this reduction, nor by the protection or deprotection steps.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been employed less frequently, probably because of the lack of selectivity that the hydride reagents have for various functionalities. 26 For the synthesis of 7, we tried the direct reduction method using various conditions (Table 1). LAH, alane, and borane were used as hydride-donor reducing agents.…”
Section: Chemistrymentioning
confidence: 99%